2003
DOI: 10.1200/jco.2003.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Good Prognosis Patients With Metastatic Germ Cell Cancer: A Prospective Study of the European Organization for Research and Treatment of Cancer Genitourinary Group/Medical Research Council Testicular Cancer Study Group (30941/TE20)

Abstract: Because of the excess of acute GI toxicity and the increased risk of tinnitus after the 3-day regimen, we recommend the 5-day regimen if four cycles of BEP are planned. If only three cycles are to be given, then the 3-day regimen is acceptable, even given the increased risk of nausea/vomiting at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 29 publications
7
77
1
2
Order By: Relevance
“…Quality assessment revealed that studies differed greatly in quality. Seven studies were considered as stronger [19,20,27,40,41,42,47], because on the whole, these studies used suitable designs, had adequate sample sizes, used validated questionnaires and comparison groups (with exception of the two prospective studies) [20,47], and had large ranges in time since treatment (with exception of the two prospective studies). Furthermore, these studies considered time since treatment in their analyses, whereas in total, only nine studies investigated whether time since diagnosis was related to one of the outcome variables [7,11,16,19,27,35,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment revealed that studies differed greatly in quality. Seven studies were considered as stronger [19,20,27,40,41,42,47], because on the whole, these studies used suitable designs, had adequate sample sizes, used validated questionnaires and comparison groups (with exception of the two prospective studies) [20,47], and had large ranges in time since treatment (with exception of the two prospective studies). Furthermore, these studies considered time since treatment in their analyses, whereas in total, only nine studies investigated whether time since diagnosis was related to one of the outcome variables [7,11,16,19,27,35,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, however, very few prospective studies have been conducted. Fossa et al 16 conducted one of the few studies using data collected from patients enrolled in a clinical trial conducted through the European Organization for Research and Treatment of Cancer. In this study, the authors compared HRQOL outcomes among men treated with 4 different chemotherapy regimens.…”
Section: Commentmentioning
confidence: 99%
“…Limited evidence suggests that although treatment is associated with a significantly increased risk of certain treatment-related side-effects (eg, fertility, neurotoxicity, and Raynaud's phenomena), 10,12 post-treatment overall quality of life may not be adversely affected by treatment approach. [13][14][15][16][17] In addition, the few prospective studies that have been published suggest that although quality of life is adversely affected during adjuvant chemotherapy and radiation therapy, levels tend to return to baseline after the completion of treatment. 16,18,19 However, several reports suggest that survivors are more likely to experience some adverse outcomes, such as anxiety, 20 chronic fatigue, 21 and sexual dysfunction.…”
mentioning
confidence: 99%
“…99 BEP given over 3 days, however, has increased short-term gastrointestinal toxicity and long-term ototoxicity. 99,101 Carboplatin should not be substituted for cisplatin due to inferior outcomes. 102,103 Thus, the original 5-day BEP regimen, therefore, is the preferred option for the management of advanced GCTs.…”
Section: Treatment Of Advanced or Metastatic Diseasementioning
confidence: 99%